Population Policies and Programmes in Singapore, 2nd edition. - Swee-Hock, Saw (ISEAS - Yusof Ishak Institute, 2016)
The second edition of Population Policies and Programmes in Singapore presents an up-to-date and comprehensive account of the government's initiatives to influence the course of fertility, and hence the rate of population growth in the island-state of Singapore since the 1960s. The varied population issues and consequences associated with the prolonged below-replacement fertility are discussed in detail. The strength of the book lies in the author's intimate familiarity with the subject acquired through some personal involvement in the formulation of population policies for the country.